PENINGKATAN KUALITAS PENDIDIKAN DAN KESEHATAN MASYARAKAT DESA LAPAO-PAO DI MASA PANDEMI COVID-19 MELALUI KULIAH KERJA NYATA (KKN) TEMATIK - Farman Farman; Nasarudin Nasarudin; Chairuddin Chairuddin; Halidin Halidin; Akbar Nasrum; Fitriyani Hali; Herlina Herlina (As-Sidanah, 2022)
This activity aims to improve the quality of life of the people of Lapao-pao Village amid the covid-19 pandemic, especially regarding health and environmental hygiene issues and children's interest in learning. The method of this activity was carried out in the form of thematic KKN, which synergizes knowledge and solves problems in the community through the concept of empowerment and fosters students in implementing the understanding that they were engaged in community life. The steps of this activity consist of preparation, implementation, and evaluation of activities. Implementation of the Community Service Program in Lapao-pao Village, Wolo District, Kolaka Regency, Southeast Sulawesi, for approximately one month starting on 3 September 2020 - 3 October 2020. Based on the activities carried out, it was concluded that all programs can be carried out well, smoothly, and realized 100%. With the implementation of these programs, it is hoped that it will be beneficial for the people of Lapao-pao Village. Especially in increasing the spirit of hard work, desire to progress, positive mental attitude, critical mindset, in the end, being able to develop themselves and maintain the health and cleanliness of the community environment.